Visual attention based detection of signs of anthropogenic activities in satellite imagery - Skurikhin, A N (2010 IEEE 39th Applied Imagery Pattern Recognition Workshop (AIPR), 2010)
With increasing deployment of satellite imaging systems, only a small fraction of collected data can be subject to expert scrutiny. We present and evaluate a two-tier approach to broad area search for signs of anthropogenic activities in highresolution commercial satellite imagery. The method filters image information using semantically oriented interest points by combining Harris corner detection and spatial pyramid matching. The idea is that anthropogenic structures, such as rooftop outlines, fence corners, road junctions, are locally arranged in specific angular relations to each other. They are often oriented at approximately right angles to each other (which is known as rectilinearity relation). Detecting rectilinear structures provides an opportunity to highlight regions most likely to contain anthropogenic activity. This is followed by supervised classification of regions surrounding the detected corner points as anthropogenic vs. natural scenes. We consider, in particular, a search for signs of anthropogenic activities in uncluttered areas.